Tasawuf hamzah fansuri - Aini, Kurrotul (Maliki Interdisciplinary Journal, 2025)
hamzah fansuri was a prominent sufi figure from the malay world who lived during the 16th to early 17th century. his thought marked a significant phase in the development of sufism in the nusantara, particularly through a philosophical approach influenced by the concept of wahdat al-wujud (unity of existence) from ibn ’arabi. in his works both in prose and poetry, especially in the form of syair hamzah fansuri elaborated on concepts such as divinity, the insan kamil (perfect human), and the spiritual journey (suluk) using symbolic and metaphorical language. he viewed all existence as a manifestation of god’s essence, and believed that the ultimate goal of human beings is to return to their divine origin through purification of the soul and ma‘rifah (gnosis). his ideas were considered controversial and were criticized by figures like nuruddin al-raniri, who regarded his teachings as deviating from islamic law (shari‘a). nevertheless, hamzah fansuri’s influence remains significant in the intellectual history of islam in southeast asia, especially in shaping the unique and poetic character of malay sufism.